2022
DOI: 10.1123/tsp.2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mindfulness-Based Intervention on Sustained and Selective Attention in Young Top-Level Athletes in a School Training Setting: A Randomized Control Trial Study

Abstract: Attention is a key success factor in elite sports. Mindfulness training is suspected to be a determinant of attention. The present study was a wait-list controlled investigation of the effects of a mindfulness-based sport psychology program on sustained and selective attention in young elite athletes (n = 137) and the effects of mindfulness training dosage on improving attention scores. In addition, long-term effects were examined. Selective and sustained attention were assessed in a pre–post design using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Regarding the enhancing effect of mindfulness intervention on other psychological outcomes such as attention and acceptance in the current study, the findings are similar to the updated evidence from Röthlin et al (2020) [38], Kittler et al (2022) [39], and Lu et al (2021) [40], which found that mindfulness training improves athletes' attention and increases awareness of the present moment. Moreover, it has been proven that the increased attention brought about by mindfulness training can lead to other positive effects such as a reduction in sport-related injury [41] and mental burnout [42].…”
Section: Intervention Effect On Psychological Outcomessupporting
confidence: 91%
“…Regarding the enhancing effect of mindfulness intervention on other psychological outcomes such as attention and acceptance in the current study, the findings are similar to the updated evidence from Röthlin et al (2020) [38], Kittler et al (2022) [39], and Lu et al (2021) [40], which found that mindfulness training improves athletes' attention and increases awareness of the present moment. Moreover, it has been proven that the increased attention brought about by mindfulness training can lead to other positive effects such as a reduction in sport-related injury [41] and mental burnout [42].…”
Section: Intervention Effect On Psychological Outcomessupporting
confidence: 91%
“…The mechanisms involved, which can act both directly and indirectly, include: neurobiological changes, the increased emotional regulation and reduction in negative emotions, such as anxiety and anger [ 74 , 75 ], increased attentional control [ 67 , 76 , 77 ], flow [ 78 , 79 ], reduced rumination and irrational beliefs (e.g., perfectionism), reduced worry and self-judgment [ 3 , 44 ], decreased experiential avoidance [ 80 ], increased positive emotions and self-efficacy [ 6 , 81 ], and even (self-)compassion [ 3 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the last two studies, one of them found that MAC improved dimensions of self-compassion and grit among female adult athletes [55]. Another one suggested that BATL improved both sustained and selective attention in young athletes and that more training in the same amount of time resulted in higher scores in the assessment [56].…”
Section: Effects Of Mindfulness-based Interventions On Mindfulness-re...mentioning
confidence: 99%